ENVIROMENTAL TECHONOLOGY AND ITS APPLICATIONS - Beneli Duarte Bispo, Luis Felipe; Freire, José Eduardo (Revista Interface Tecnológica, 2020)
With exponential technological growth, there are constant changes in its development so that it can consciously adapt to the environment and society that use it. A good management of a technology project is an important point for its completion and efficiency, thus avoiding possible impacts and future problems. This article aims to present the results of the application of environmental technology in a mining company, called Vale S.A.. As a methodology, a bibliographic survey relevant to the topic and a case study was used. The conclusions of this study indicate the main practices exercised through research and applications throughout technological and environmental development, which is of great relevance today, aimed at solving problems, reducing environmental impact and innovating proposals and processes, mainly counting with the advancement of technology and the way in which it is managed. However, to achieve objectives and goals, one can observe the constant need for improvements in existing processes and in the development of new ones.